Secure and privacy preserving IoT gateway for home automation. (September 2022) - Demir, Simge; Şimşek, Şevval; Gür, Sinem; Levi, Albert
Highlights: Addressing security and privacy issues in IoT devices in a scalable way Providing zero-knowledge mutual authentication in home automation systems Anonymous identification based on Idemix credential system Introducing privacy preserving layer to obfuscate the communication Abstract: Internet of Things (IoT) applications have become widely popular for academic and industrial purposes in recent years. One of the most important applications in IoT is Home Automation Systems. Home Automation Systems consist of a number of devices in the home network that allow the homeowners to monitor and control their home from anywhere. However, connectivity to the internet and the simplicity of such devices raise a number of security and privacy concerns. In this paper, we propose a privacy preserving and secure identification and authentication model for Home Automation Systems. In our model, a trusted middleware-layer is developed to ensure a secure and scalable communication platform and provide privacy for the users. We propose a zero knowledge mutual verification and authentication protocol. Meanwhile, for privacy preservation we introduce a communication model by implementing fake proofs with the aim of hiding the identity of the IoT devices. Furthermore, the communication over MQTT is obfuscated by the Home Management System to avoid intrusions and to prevent third parties from tracing the communication. Experiments are conducted for different communication scenarios and the security analysis for the protocol is presented. Graphical Abstract: Image, graphical abstract